Available treatment methods for endometriosis - Krupa, Adrianna; Padała, Olga; Putowski, Maciej; Konopelko, Michał; Piasek, Ewa (Journal of Education, Health and Sport, 2019)
Introduction and and purpose of paper: The aim of this paper was to present modern methods of treatment for endometriosis. Endometriosis is a chronic inflammatory condition of women that is characterized by the implementation of endometrial tissue outside the uterus. It affects 7 to 15% of menstruating women, and 35 to 50% of women treated for infertility. State of knowledge: Diagnosis of endometriosis is made on the basis of well-collected gynecological history, clinical examinations and imaging techniques. The golden standard for diagnostics is laparoscopy with subsequent histological examination of the material collected during the procedure. Among the methods of treatment in women with endometriosis, pharmacological and surgical treatment is applied. The pharmacological agents most commonly used in endometriosis are: combined hormonal contraceptives, progestins and anti-progestins, GnRH agonists and antagonists, aromatase inhibitors, Danazol and non-steroidal anti-inflammatory drugs (NSAIDs). Pharmacological treatment is only symptomatic, not cytoreductive, therefore, to remove endometriosis lesions, surgery should be performed. There are two ways to perform surgery: laparotomy and laparoscopy. Surgical treatment of endometriosis may be associated with local excision of lesions and sometimes even removal of the entire organ. Treatment should be conducted in consultation with the patient and her wishes. Conservative treatment is most commonly used among women of reproductive age. Summary: The pharmaceutical or surgical treatment require an individual approach and deliberated informed consent of patient. Pharmacological treatment is only symptomatic, not cytoreductive, therefore, to remove endometriosis lesions, surgery should be performed.